Structural overshoot of tree growth with climate variability and the global spectrum of drought-induced forest dieback - Jump, Alistair S. (2017)
Ongoing climate change poses significant threats to plant function and distribution. Increased temperatures and altered precipitation regimes amplify drought frequency and intensity, elevating plant stress and mortality. Large-scale forest mortality events will have far-reaching impacts on carbon and hydrological cycling, biodiversity, and ecosystem services. However, biogeographical theory and global vegetation models poorly represent recent forest die-off patterns. Furthermore, as trees are sessile and long-lived, their responses to climate extremes are substantially dependent on historical factors. We show that periods of favourable climatic and management conditions that facilitate abundant tree growth can lead to structural overshoot of aboveground tree biomass due to a subsequent temporal mismatch between water demand and availability. When environmental favourability declines, increases in water and temperature stress that are protracted, rapid, or both, drive a gradient of tree structural responses that can modify forest self-thinning relationships. Responses ranging from premature leaf senescence and partial canopy dieback to whole-tree mortality reduce canopy leaf area during the stress period and for a lagged recovery window thereafter. Such temporal mismatches of water requirements from availability can occur at local to regional scales throughout a species geographical range. As climate change projections predict large future fluctuations in both wet and dry conditions, we expect forests to become increasingly structurally mismatched to water availability and thus overbuilt during more stressful episodes. By accounting for the historical context of biomass development, our approach can explain previously problematic aspects of large-scale forest mortality, such as why it can occur throughout the range of a species and yet still be locally highly variable, and why some events seem readily attributable to an ongoing drought while others do not. This refined understanding can facilitate better projections of structural overshoot responses, enabling improved prediction of changes in forest distribution and function from regional to global scales.